Estimates of Total Dietary Folic Acid Intake in the Australian Population Following Mandatory Folic Acid Fortification of Bread - Jacinta Dugbaza; Judy Cunningham (Journal of Nutrition and Metabolism)
Mandatory folic acid fortification of wheat flour for making bread was implemented in Australia in September 2009, to improve the dietary folate status of women of child-bearing age, and help reduce the incidence of neural tube defects in the population. This paper presents estimates of folic acid intake in the target population and other subgroups of the Australian population following implementation of the mandatory folic acid fortification standard. In June/July 2010 one hundred samples from seven bread categories were purchased from around the country and individually analysed for the amount of folic acid they contained. A modification to the triple enzyme microbiological method was used to measure folic acid in the individual bread samples. The folic acid analytical values together with national food consumption data were used to generate estimates of the population’s folic acid intake from fortified foods. Food Standards Australia New Zealand’s (FSANZ) custom-built dietary modelling program (DIAMOND) was used for the estimates. The mean amount of folic acid found in white bread was 200 μg/100 g which demonstrated that folic-acid-fortified wheat flour was used to bake the bread. The intake estimates indicated an increase in mean folic acid intake of 159 μg per day for the target group. Other sub-groups of the population also showed increases in estimated mean daily intake of folic acid.